Prevalencia de la infección por Helicobacter pylori según ensayo de la ureasa en pacientes derivados a la Unidad de Endoscopía del Hospital Clínico de la Universidad de Chile - Toledo A., Héctor; Defilippi C., Carlos; Madrid S., Ana María; Defilippi G., Claudia; Vallejos M., Cristián; Cáceres L. , Dante; Venegas S. , Mauricio (Revista Hospital Clínico Universidad de Chile, 2007)
Background: Helicobacter pylori is a pathogenic bacterium that infects a significant number of individuals. In Chile about 79% of the population is colonized. Aims: This study evaluate the prevalence of the H. pylori infection in symptomatic outpatients. Materials and Methods: 276 non selected patients were enrolled from Endoscopic Unit of Clinical Hospital of the University of Chile. The bacterium was detected by urease test. Results: H. pylori infection was found in 44,9% patients. Infection was higher in younger patients, 53,8% between 21-60 years, and was lower in older patients, 25,6% in older than 60 years. The risk of being H. pylori carrier is twofold higher in persons younger than 60 years as compared to those older than 60 years. Conclusion: The age would be modifier factors for H. pylori infection risk.